Rehabilitation Exercises for Dysfunction of the Scapula: Exploration of Muscle Activity Using Fine-Wire EMG. Issue 10 (August 2021) - Berckmans, Kelly R.; Castelein, Birgit; Borms, Dorien; Parlevliet, Thierry; Cools, Ann
Background: Scapular muscle activity during shoulder exercises has been explored with surface electromyography (EMG). However, knowledge about the activity of deeper-layer scapular muscles is still limited. Purpose: To investigate EMG activation of the deeper-layer scapular stabilizers (levator scapulae [LS], rhomboid major [RM], pectoralis minor [Pm] muscles) together with superficial muscle activity (upper [UT], middle [MT], and lower trapezius [LT] and serratus anterior [SA]) during 4 exercises often used for training scapular function. Based on the amplitude EMG of the deeper-layer muscles, scapular muscle activation ratios for the 4 exercises were calculated, hereby providing knowledge of the optimal muscle balance. Study Design: Descriptive laboratory study. Methods: A total of 26 healthy participants performed 4 shoulder exercises (side-lying external rotation [ER], side-lying forward flexion, prone horizontal abduction with ER, and prone extension) while simultaneously measuring scapular muscle activity. Intramuscular electrodes were used for the deeper layer, in contrast to surface electrodes for the superficial muscles. All data were normalized to percentage of maximal voluntary isometric contraction (%MVIC), and the activation ratios (the muscle activity of the deeper layer relative to the other muscles) were calculated. A 1-way analysis of variance with Bonferroni correction was applied for statistical analysis. Results: Moderate activity was found in all exercises for the LS and RM (25%-45% MVIC). The Pm resulted in low activity during both side-lying exercises (13%-18% MVIC). Ratios involving LS or RM showed values >1 for all exercises (1.28-12.41) except for LS/MT, LS/LT, and LS/RM (0.85-0.98) during side-lying ER, and LS/MT, RM/MT and RM/LS (0.85-0.99) during side-lying forward flexion. Likewise, values <1 were found when MT (0.85) and LS (0.99) were involved with RM in the numerator during side-lying forward flexion. Ratios with Pm in the numerator showed values <1, apart from the ratios with UT and SA in the denominator. Conclusion: The study provides extended knowledge about the deeper-layer scapular muscle activity and related ratios during the 4 shoulder exercises mentioned here. Putting theory into practice, based on our results, we advise both side-lying exercises to be performed to strengthen LT and MT, even in case of hyperactivity of the Pm. However, the 4 exercises should be given carefully to patients with hyperactivity in the LS and/or RM. Clinical Relevance: The findings of this study may assist clinical decision making in exercise selection for restoring scapular function.